The Challenge of Transition - Pringle, Tim. author. aut Link
X, 218 p.
Keywords: This book explores the transformation of employment relations, the rise of worker protest and the reform of trade union practice to ask how successfully the state-socialist trade unions have adapted to their new role of representing the rights and interests of workers.